2017
DOI: 10.3332/ecancer.2017.749
|View full text |Cite
|
Sign up to set email alerts
|

Brain imaging before primary lung cancer resection: a controversial topic

Abstract: ObjectiveInternational and national recommendations for brain imaging in patients planned to undergo potentially curative resection of non-small-cell lung cancer (NSCLC) are variably implemented throughout the United Kingdom [Hudson BJ, Crawford MB, and Curtin J et al (2015) Brain imaging in lung cancer patients without symptoms of brain metastases: a national survey of current practice in England Clin Radiol https://doi.org/10.1016/j.crad.2015.02.007]. However, the recommendations are not based on high-qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…To our knowledge, this is the first study to characterize practice patterns of brain imaging among patients with a new diagnosis of stage IA NSCLC in a nationally representative cohort in the United States. However, our results echo previous, non-population-based studies from around the world that reported on the general overuse 2,18,19 and clinical variation 9,20 of brain imaging in similar patients.…”
Section: Discussionsupporting
confidence: 89%
“…To our knowledge, this is the first study to characterize practice patterns of brain imaging among patients with a new diagnosis of stage IA NSCLC in a nationally representative cohort in the United States. However, our results echo previous, non-population-based studies from around the world that reported on the general overuse 2,18,19 and clinical variation 9,20 of brain imaging in similar patients.…”
Section: Discussionsupporting
confidence: 89%
“…Our study in 411 patients with lung cancer demonstrates the importance of pre-therapeutic cranial MRI, which is still a matter of debate [ 10 , 11 ], even if neurologic metastases [ 12 ] are common in lung cancer. Following the results of our study, we can distinguish SCLC from NSCLC on initial diagnostic work-up.…”
Section: Discussionmentioning
confidence: 99%
“…Our study in 411 patients with lung cancer demonstrates the importance of pre-therapeutic cranial MRI, which is still a matter of debate [9,10], even if neurologic metastases [11] are common in lung cancer.…”
Section: Discussionmentioning
confidence: 72%